Collectivist and Individualist Cultures in the Digital Space: A Descriptive Content Analysis of Self-Disclosure on Instagram Feeds among Indonesian and United States College Students - Rachmah, Fitri Annisa; Ramadhan, Affan Neskisyah; Narimawati, Umi (PINISI Discretion Review, 2025)
This study examines the differences in self-disclosure patterns on Instagram Feeds between Indonesian and United States college students through the lens of collectivist and individualist cultural orientations. Using a descriptive qualitative approach and document analysis of selected scholarly literature, the findings reveal that Indonesian users tend to disclose themselves indirectly, highlight group activities, and apply strict privacy settings to maintain social harmony. In contrast, U.S. users are more likely to disclose personal achievements directly and explicitly, with more relaxed privacy settings to support self-expression and personal branding. These findings are analyzed using Communication Privacy Management (CPM) Theory and Hofstede’s Cultural Dimensions, demonstrating that collectivist and individualist cultural values significantly shape self-disclosure practices and privacy boundary management in digital spaces.